Revisiting the role of audit and compensation 'committees' characteristics in the financial performance of the non-financial sector through the lens of the difference generalised method of moments - Habib Ur Rahman; Asif Ali (Cogent Business & Management, 2022)
This study aims to analyse the role of audit and compensation committees' characteristics in the financial performance of the non-financial sector of Pakistan. For this purpose, we collect data from 2009 to 2020 for 70 non-financial firms selected through stratified random sampling. Theoretically, the committees' characteristics and financial performance are jointly determined, creating some estimation issues in the panel setting. Therefore, the issue of endogeneity, the dynamic data-generating process and autocorrelation between the residuals needs attention to arrive at consistent and unbiased estimates. To overcome these estimation issues, we estimate the dynamic panel models using difference GMM under the Arellano-Bond framework to arrive at unbiased and consistent estimates. The estimates of this study reveal that the characteristics of the audit and compensation committees improve the overall financial performance of the non-financial sector of Pakistan. The specific estimates of the committee's characteristics reveal that the audit and compensation committee independence, audit and compensation committee meetings, and audit committee size enhance the financial performance of the non-financial sector of Pakistan. These findings strengthen the idea that the audit and compensation committee should be independent, which helps develop strong internal controls. Therefore, a key policy priority should be to plan for implementing some parts of the Sarbanes Oxley Act in Pakistan. Surprisingly, the audit committee's existence and the compensation committee head's independence deteriorate the financial performance of the non-financial sector of Pakistan. This study has raised important questions about the compensation committee chairman's independence that need further investigation.
Keywords: 650; Audit committee; financial performance; committee Independence; compensation committee; non-financial sector